An Overview of Animal Models and Symptomatic Treatment of Parkinson’s disease - Patil, Pooja; Chaware, Vitthal; Redasani, Vivekkumar (Asian Journal of Pharmaceutical Research and Development, 2023)
The broad theory indicate that neurological ailment is caused by intricate interactions between environmental and genetic factors is supported using animal models to better understand the the cause and pathogenesis of Parkinson's disease (PD), as well as its cellular and molecular mechanisms. The more recent models use genetic manipulations that either introduce mutations similar to those found in familial cases of PD (a-synuclein, DJ-1, PINK1, Parkin, etc.) or selectively disrupt nigrostriatal neurons (MitoPark, Pitx3, Nurr1, etc.). "Classic" models are based on neurotoxins that specifically target catecholaminergic neurons. All of these together each model has its own benefits and drawbacks. The use of medication, deep brain stimulation, and physical therapy has been optimised for the symptomatic treatment of the motor symptoms of Parkinson disease (PD). L-dopa, several dopamine agonists, inhibitors of MAO-B and catechol-o-methyltransferase (COMT), and amantadine are among the pharmacotherapies available.